Antioxidant Activity of Ethanol Extract of Polygonum pulchrum Blume - Sadino, Asman; Sahidin, Idin; Wahyuni, Wahyuni (Universitas Padjadjaran, Indonesia)
The use of antioxidants from natural resources has attracted increasing interest. One of theplant that was empirically used as an antioxidant dietary supplement was Polygonum pulchrumBlume (P. pulchrum Blume). This study aimed to investigate antioxidant activityof roots, stems, leaves and flowers ethanol extract of P. pulchrum Blume. The extract wasobtained by maceration method using ethanol solvent. Antioxidant activity was determinedwith 1,1-diphenyl-picrylhydrazyl (DPPH) method. We found that ethanol extracts of P. pulchrumBlume roots and stems had strong antioxidant activity with IC50 values of 25.2 mg/land 43.26 mg/l, respectively. Ethanol extract of flowers had the weakest antioxidant activitywith IC50 value of 202.96 mg/l. Vitamin C had very strong antioxidant activity with IC50value of 3.97 mg/l. In conclusion, our study revealed that ethanol extract of Polygonumpulchrum Blume roots and stems had strong antioxidant activity. Therefore, P. pulchrumBlume might be potential as an excellent source for natural antioxidant agents for medicalapplication.Keywords: Polygonum pulchrum Blume, DPPH, antioxidant, maceration, ethanol